Studying Breastfeeding Discourse in Armenia: A Sociological Insight - Lilit Babayan (Banber Erevani Hamalsarani. Sots'iologia, 2023)
This paper discusses the role of the societal discourse in the construction of breastfeeding practices. It argues that societal discourse is crucial to the constitution of those practices, and that understanding the underlying circumstances of the breastfeeding situation anywhere in the world requires looking not only at the social reality itself but at the discourse that represents, reflects and constructs it. Proposing Armenia as a study case, the paper outlines the various sources of modern discursive practices around the feeding of children in Armenia, including pre-industrial customs, soviet political ideology, and modern Western values. Doing so, it proposes a new approach to studying breastfeeding practices through the prism of various discursive influences.